1998
DOI: 10.1002/1529-0131(199807)41:7<1318::aid-art24>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous ischemic gallbladder necrosis in the catastrophic antiphospholipid syndrome

Abstract: A 29-year-old woman was referred for abdominal pain. Results of tests for lupus anticoagulant and antibodies to phosphatidylserine and to P,-glycoprotein I were positive, but the patient had no features of systemic lupus erythematosus (SLE). Abdominal ultrasonography showed a thickening of the gallbladder wall without cholelithiasis. A surgical procedure revealed necrotic areas of the gallbladder wall, and a cholecystectomy was performed. Histologic examination of the gallbladder showed multiple thrombi and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…To our knowledge, ours is the second case of acute acalculous cholecystitis in a patient suffering from CAPS [12] that has been published. It might be argued that in our patient AAC was just a secondary event, because the occurrence of AAC is known as a possible complication of major surgery; however, this is not supported by the occurrence of further ischemic manifestations of other organs.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, ours is the second case of acute acalculous cholecystitis in a patient suffering from CAPS [12] that has been published. It might be argued that in our patient AAC was just a secondary event, because the occurrence of AAC is known as a possible complication of major surgery; however, this is not supported by the occurrence of further ischemic manifestations of other organs.…”
Section: Discussionmentioning
confidence: 80%
“…Dessailloud et al showed that antiphospholipid antibody syndrome can produce ACC [15]. They found multiple thrombi in the gallbladder veins and no vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in both cases abdominal pain was the presenting symptom. Although hepatic and renal involvement is common in the published APS cases, gallbladder involvement is described only in a few [15]. The small number of fragmented red cells in the peripheral blood smear is also rare [4].…”
Section: Discussionmentioning
confidence: 99%